Traditional Heritage Boat Survey : Grand Canal, Royal Canal, Barrow Navigation : an initiative of the Waterways Ireland Heritage Plan 2016-2020.: Grand Canal, Royal Canal, Barrow Navigation : an initiative of the Waterways Ireland Heritage Plan 2016-2020. ([2016]) - Waterways Ireland,; Heritage Boat Association,; Inland Waterways Association of Ireland,; Meitheal Mara (Community boatyard),
No abstract available